1998
DOI: 10.1021/jp9730196
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Equilibria of C1to C4Alkanes, CO2, and SF6on Silicalite

Abstract: Adsorption isotherms of methane, ethane, propane, n-butane, isobutane, carbon dioxide, and sulfur hexafluoride were measured gravimetrically on silicalite crystals at temperatures ranging from 3 to 81 °C and at pressures up to 2000 kPa. A virial equation was used to correlate the experimental data and to calculate the isosteric heats of adsorption and the limiting heats of adsorption at zero loading. The adsorption isotherms of isobutane exhibit inflection points at loadings of 4−6 molecules/unit cell in a cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
183
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(213 citation statements)
references
References 21 publications
29
183
0
1
Order By: Relevance
“…Adsorption isotherms of isobutane have been reported by Sun et al 16 and Zhu et al 14 15,64 Here we investigate the sorption behavior of branched alkanes at higher loadings. As a first approximation we have assumed that the interaction CH group of the branched alkane with the zeolite is identical to the interaction of a CH 2 group (see Table 2).…”
Section: Branched Alkanesmentioning
confidence: 83%
See 2 more Smart Citations
“…Adsorption isotherms of isobutane have been reported by Sun et al 16 and Zhu et al 14 15,64 Here we investigate the sorption behavior of branched alkanes at higher loadings. As a first approximation we have assumed that the interaction CH group of the branched alkane with the zeolite is identical to the interaction of a CH 2 group (see Table 2).…”
Section: Branched Alkanesmentioning
confidence: 83%
“…the heats of adsorption of isobutane have been obtained by Zhu et al 14 and Sun et al 16 who obtained -46.7 and -56 kJ/ mol, respectively. The reasons for this large difference are unclear.…”
Section: Branched Alkanesmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in itself not unusual, but in both cases the loading overshoots the 4 molecules per unit cell without an inflection in the isotherm. Many studies, both experimental and computational, have shown that the isotherms of bulky molecules, like isobutane, 11,12,37,38 in MFItype silica show an inflection as the molecules need an extra ''push'' to adsorb in the narrow channels once the 4 intersections per unit cell are occupied. The overshoot can also not be temperature related, since the highest temperature of Song et al is still lower than the lowest temperature of Cavalcante et al, the former being correctly reproduced.…”
Section: Resultsmentioning
confidence: 99%
“…These probabilities can be further optimized depending on the details of the simulations. 4 Comparison of the experimental data 25,26 for pure component isotherms for (a) methane, (b) ethane, (c) propane, and (d) n-butane in MFI at 300 K with CBMC simulations. [22][23][24] A simple approach to describe the alkane molecules is to use the united-atom model, in which CH 3 , CH 2 , and CH groups are considered as single interaction centers.…”
Section: Cbmc Simulation Techniquementioning
confidence: 99%